The Effect Of Honey Give As Oral Drops In Precipitating Epithelialization Of Lateral Palatal Defects Post TwoFlap Palatoplasty - Kreshanti, Prasetyanugraheni; Sudjatmiko, Gentur; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2012)
Background : Two-flap palatoplasty, which is a very common technique used including in our institution, will result in lateral palatal defects without any periosteal coverage. Faster epithelialization is expected to decrease wound contraction thus reducing scar formation, and in the long run will result in good maxillary growth. In our institution, the retrospective study showed a fair maxillary growth (mean GOSLON score=3.5). Thus, we explore possibilities to precipitate the epithelialization process in pursuit of good maxillary growth in the future.Method :This is a prospective cohort study conducted in Cipto Mangunkusumo Hospital, on consecutive patients who underwent two-flap palatopasty from October 2010-February 2011. We followed up these patients weekly for 4 consecutive weeks to observe the rate of epithelialization of the lateral palatal defects.Result : Two-flap palatoplasty was performed in 48 patients, 23 among them were given honey as oral drops. Eighty-seven point five percent had unilateral complete cleft lip and palate and 12.5% had bilateral complete cleft lip and palate. Faster epithelialization of the lateral palatal defects post two-flap palatoplasty was significantly in!uenced by intraoral honey application on the wound as oral drops (RR 2.1, 95% CI 1.314 - 3.391, p < 0.001).Conclusion: Honey given as oral drops significantly precipitates the epithelialization process of the lateral palatal defects post two flap palatoplasty 2.1 times faster.